Formulasi Sediaan Lip Cream dengan Pewarna Alami Ekstrak Buah Senggani (Melastoma malabathricum L.): Lip Cream Formulation with Natural Coloring Senggani Fruit Extract (Melastoma malabathricum L.) - Khoiriyah Anbar Mufidah; Febrina Mahmudah; Laode Rijai (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Senggani (Melastoma malabathricum L.) is a wild plant that has anthocyanin compounds which are red, purple and blue pigments in plants that can be used as natural dyes. So, to increase the use value of the senggani plant, senggani fruit extract is used as a natural coloring agent in lip cream preparations. Senggani fruit was extracted, then formulated. The quality of the preparation is determined through evaluation of physical characteristics (organoleptic test, homogeneity test, dispersion test, adhesion test, viscosity test and pH test), physical stability test (freeze thaw method and room temperature) for 16 days, evaluation of the safety of the irritation test (method patch test) and acceptability (hedonic test method). The results obtained were the lip cream preparation formula using senggani fruit extract with a concentration of 5%, 10%, and 15% producing purple, reddish purple, and purplish red colors, respectively. The results of the evaluation of the physical characteristics of all preparations included the aroma of rose flowers, semisolid consistency, homogeneous and has a viscosity, dispersibility, adhesion, and pH that meet the pharmaceutical requirements of lip cream preparations. The results of the physical stability test of the three formulas showed that all preparations were stable, with organoleptic, homogeneity, pH, and viscosity that met the range and there was no phase separation. The results of the irritation test of the preparations showed that the preparations did not irritate and the results of the acceptability of the preparations in terms of color and texture of the preparations were preferably panelists at a concentration of 10% and in terms of aroma, preferably panelists at a concentration of 5%.